Social media for government : a practical guide to understanding, implementing, and managing social media tools in the public sphere - Khan, Gohar (Springer, 2020)
Contents: Foreword; Preface; Organization; Acknowledgements; Contents; List of Figures; List of Tables; List of Case Studies; List of Screenshots; 1 Introduction to Social Media; Abstract; 1.1 Web 1.0, Web 2.0, and Social Media; 1.1.1 World Wide Web; 1.1.2 Web 1.0; 1.1.3 Web 2.0; 1.1.4 Web 3.0; 1.1.5 Social Media; 1.1.6 Core Characteristics of Social Media; 1.1.7 Types of Social Media;